The meaning of happiness and religiosity for pre-prosperous family; study in Manado, Bandar Lampung, and Yogyakarta - Suyatno, Ladiqi; Ahmad, Rajafi; Naili Adilah, Hamhij (2020)
Based on research conducted in 2017, this article wants to explain correlation between happiness and religiosity for pre-prosperous families. The research took place in Manado, North Sulawesi Province, Bandar Lampung, Lampung Province, and Yogyakarta. This study wanted to prove a popular assumption that religious pre-prosperous people are typically not happy. It found a positive and significant relationship between happiness and religiosity in pre-prosperous families in Yogyakarta, but not in Manado and Bandar Lampung. The highest level of happiness is in Yogyakarta and the highest level of religiosity is in Manado. This difference occurs because the concept of happiness for religious pre-prosperous families in Manado, Yogyakarta and Bandar Lampung has different point of views and uniqueness.